Deaggregation of Human Platelets Aggregated by Thrombin - Kinlough-Rathbone, R L; Perry, D W; Packham, M A; Mustard, J F (Thrombosis and Haemostasis, 1985)
Human platelets that have undergone the release reaction do not deaggregate readily. We examined conditions under which washed human platelets can be deaggregated after they have undergone an extensive release reaction induced by thrombin (1 or 5 U/ml). To make fibrinogen receptors unavailable, either CP/ CPK (or apyrase) was used to remove released ADP, or PGEi was used to increase cAMP. Chymotrypsin was used to digest proteins that might link platelets, and heparin to interact with released proteins and interfere with their binding to platelets and to each other. Individually, none of these caused deaggregation; heparin did not inhibit the effect of thrombin because no antithrombin III was present. Platelets exposed to thrombin (1 U/ ml) which was neutralized at 90 sec by hirudin, could be deaggregated by combinations of CP/CPK (or apyrase) and chymotrypsin, or PGE1 and chymotrypsin. When a higher concentration of thrombin was used (5 U/ml) these combinations caused platelets to deaggregate only when heparin was added before thrombin induced the release reaction. Thus, when extensive release occurs three mechanisms may come into play to link human platelets: one that requires the fibrinogen receptor; a heparin-sensitive reaction that may involve the binding of released proteins; and a linkage that can be disrupted only by proteolysis, providing the other two mechanisms are also inhibited.
Keywords: Platelet deaggregation; Thrombin-induced aggregation; Release reaction